Influence of alloying elements and aging treatment on the phase transformation and shape memory behavior of Cu-A1-Ni shape memory alloys [electronic resource] - Safaa Najah Saud, 1985-, author (2014)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2014